RESTORATIVE JUSTICE FOR CHILDREN IN CONFLICT BY LAW REVIEWED LAW NUMBER 11YEAR2012ABOUT THE JUVENILE CRIMINAL JUSTICE SYSTEM - Aruf Bahirra; Ismaidar; Aulia Rahman Hakim Hasibuan (Journal of International Islamic Law, Human Right and Public Policy, 2026)
This study examines the application of restorative justice to children in conflict with the law from the perspective of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (SPPA Law). The purpose of the study was to analyze the application of restorative justice principles, identify obstacles to their implementation, and assess the extent to which the juvenile justice system in Indonesia has prioritized the best interests of children. This study uses a normative juridical method with a statutory approach and conceptual approach, supported by secondary data in the form of laws and regulations, legal literature, and previous research results. The results of the study show that normatively, the SPPA Law has provided a strong legal basis for the application of restorative justice through the Diversion mechanism as stipulated in Articles 6-15. The main principle of the juvenile justice system emphasizes protection, justice, the best interests of children, and makes detention and punishment as the last resort (ultima ratio) as stated in Article 2 letters i and j. However, empirically, the implementation of this principle is not optimal. Diversion often fails to be carried out due to the lack of understanding of the authorities of Article 9 and Article 10 which regulate the consent of victims and the limits of minor crimes. In addition, the implementation of child protection as stipulated in Articles 30-38 has not been maximized, because children are still often detained even though they do not meet the conditions of detention.